Peningkatan Produktivitas Pemasaran Produk UMKM Pempek Acen dengan Pendekatan Analisis SWOT dan DMAIC - Fandy Liyanto; Yohanes Dicka Pratama (Universitas Mercu Buana, 2020)
After conducting interviews it is known that the marketing activities implemented byPempek Acen SME’s have not been running optimally so that it causes the low profitsobtained by Pempek Acen SME’s. To formulate an appropriate marketing strategy, a SWOTanalysis is carried out to determine the strengths, weaknesses, opportunities and threats ofPempek Acen SME’s. Then an improvement is made using the DMAIC structure. First theidentification of current conditions at SMEs is carried out, then measurements are made toselect the issues to be overcome, then analyze the main causes of problems using a fishbonechart, then improvements are made. Implementation of improvements carried out includeconducting promotional activities using social media, making coupons for customers whobuy back Pempek SME’s Pempek Acen products and adding pempek variants to PempekAcen SME’s products. After the implementation of the improvement, there was a decrease inthe gap between the number of products produced and sold, an increase in the level ofcustomer loyalty and an increase in productivity of 1,10235 to 1,13714 after implementationof the improvements. From these data, it can be seen an increase in productivity by 0.03479or equivalent to 3.479%.